Selective surface modification of SS304 using hybrid powder-mixed EDC process. (2nd January 2022) - Yadav, Abhishek; Mohanty, Shalini; Dwivedi, Suryank; Dixit, Amit Rai
ABSTRACT: The present study acclaims the influence of hybrid powders (MoS2 +W) mixed dielectric fluid on the surface properties of SS304 by the electro-discharge coating (or EDC) process. Hard, wear-resistant, and lubricating surfaces are produced using different blending ratios of the powders infused in the dielectric liquid. The combined effect of both powders on the substrate's surface properties is studied. The process performance is evaluated in terms of wear analysis, surface roughness, coefficient of friction, micro-hardness, and compositional study at different peak current and duty factors. The experimental results show an aggregate increment of micro-hardness from 119.3% to 255.2% compared to substrate. The average surface roughness increases (2.69–4.32 μm) with an increase in tungsten content (from 5% to 50%) in the dielectric and decreases with MoS2 content. The wear test results reveal a substantial decrease in coefficient of friction (COF = 0.104) with maximum concentration of MoS2 and 0.274 for maximum tungsten.